Khotmil Qur’an di Masjid Zainul Muttaqin Waru Tingkatkan Kesadaran Ibadah Selama Ramadhan - Irfan Nufa Sagita (Universitas Pahlawan Tuanku Tambusai, 2026)
Ramadan is a strategic momentum for enhancing the quality of worship and spirituality among Muslims. However, low community participation in collective religious activities particularly khotmil qur'an (Qur'an completion recitation) has been a tangible issue in the Bandilan neighborhood, Kedungrejo, Waru, Sidoarjo. This community service activity aims to optimize the implementation of khotmil qur'an at Masjid Zainul Muttaqin as a means of increasing worship awareness, strengthening Islamic brotherhood, and empowering mosque-based communities. The Asset-Based Community Development (ABCD) approach was employed, with data collection through in-depth interviews with mosque administrators and participatory observation. The activity was conducted from March 6-9, 2025, during Ramadan evenings following tarawih prayers. Results indicated a significant increase in congregant participation from 3-5 to more than 20 per evening the formation of three structured recitation groups, and improvements in Qur'an recitation quality and collective worship consciousness. The activity also strengthened social solidarity and affirmed the central role of the mosque as an institution for Muslim community empowerment.